Kebijakan Trade Remedies Amerika Serikat untuk Produk Panel Surya: Peluang dan Tantangan Ekspor Indonesia - Pradnyawati; Maheralia, Resti (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2025)
In April 2025, the United States (US) imposed anti-dumping duties (ADD) and countervailing duties (CVD) on solar panel imports originating in Malaysia, Cambodia, Thailand, and Vietnam. The imposition of ADD and CVD for the four ASEAN countries is very high, reaching 271.28% for ADD and 3,403.96% for CVD. This article aims to review the imposition of these dual trade remedies instruments and map Indonesia's opportunities to become the largest solar panel exporter to the US. The descriptive analysis in this study reviews various data and information from several sources, such as reports from the United States Department of Commerce (USDOC) and the United States International Trade Commission (USITC), as well as related journals. This article also discusses efforts that Indonesia can undertake to support solar panel exports to the US. The results of the analysis indicate that Indonesia has the capacity and opportunity to become the largest solar panel exporter to the US after the four ASEAN countries that are Indonesia's main competitors are subject to ADD and CVD. However, Indonesia needs to maximize supporting factors and overcome inhibiting factors to develop the solar panel industry. This study is expected to elaborate on Indonesia's opportunities to become the largest exporter of solar panels to the US. The Indonesian government is also expected to actively monitor so that solar panel manufacturers sell their products at a reasonable price and do not receive countervailable subsidies.